CGIAR Excellence in Breeding Platform - Plan of Work and Budget 2019 - CGIAR Excellence in Breeding Platform (CGIAR Excellence in Breeding Platform, 2019)
The CGIAR Excellence in Breeding Platform has been established to enable change within CGIAR breeding networks toward higher rates of genetic gain and scale of impact per dollar invested. The Crops to End Hunger Initiative has been established by the funders to achieve the same outcome, and EiB is developing specific measures to reflect the involvement of the Initiative.